The influence of brand ambassador on brand image in Social Media - Frederico Morais and Billabong Brand - Jardim, Rita Maria Santos (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence